(untitled) (Revista Justiça do Direito, 2024)
This article aims to investigate the theoretical bases of the dichotomy of the institute of error in criminal law, especially based on the changes introduced by the edition of Law No. 7,209, of July 11, 1984, which changed the entire General Part of Brazilian Penal Code, Decree-Law nº 2,848, of December 7, 1940. Through a bibliographical research, type error and prohibition error types, existing in Brazilian criminal law, are analyzed. It is concluded that the change in dichotomy in the treatment of error was not just a change in the nomenclature of the institute, as it changes the very substrate of error treatment, which in the error of fact-error of law dichotomy had as objects the fact and the law, respectively; and starts to have as its objects, in the prohibition error-type error dichotomy, the criminal type and the awareness of illegality.